Influence of Hybrid Steel –Polypropylene Fibers on the Mechanical Properties of Normal Concrete (University of Thi-Qar Journal for Engineering Sciences, 2023)
This paper purposes is o study the influence of hybrid Steel-Polypropylene fibers on workability , compressive strength, splitting strength , and modulus of elasticity of ordinary concrete. For this purpose four mixes in addition to a control normal concrete mixture were prepared. The volume of steel fiber was ( 0.75% and 1.5%) and the volume of polypropylene fiber was (0.15% and 0.3 %) . Results show that all concrete mixes including hybrid fiber had lower slump flow than the control mix (0%) .In comparison to other forms of concrete without fibers, hybrid concrete with steel and polypropylene fibers shown an increase in compressive, splitting, and elasticity modulus. According to the test results, the hybridization ratio (1.5% steel and 0.3% polypropylene) maximum increase ratio in compressive and splitting tensile strengths of 32% and 69%, respectively, above the reference mix.